2022
DOI: 10.3390/s23010363
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Exercise Classification with Single-Camera Pose Detection and Machine Learning

Abstract: Access to healthcare, including physiotherapy, is increasingly occurring through virtual formats. At-home adherence to physical therapy programs is often poor and few tools exist to objectively measure participation. The aim of this study was to develop and evaluate the potential for performing automatic, unsupervised video-based monitoring of at-home low-back and shoulder physiotherapy exercises using a mobile phone camera. Joint locations were extracted from the videos of healthy subjects performing low-back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Numerous research studies have employed ML models using BlazePose keypoint data to predict falls in real-time scenarios [29,30]. To our knowledge, the work of Arrowsmith et al is the only other approach utilizing BlazePose for classifying physiotherapy exercises [31]. However, there was no emphasis on evaluating exercise performance, and the ML models were not trained or tested on actual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research studies have employed ML models using BlazePose keypoint data to predict falls in real-time scenarios [29,30]. To our knowledge, the work of Arrowsmith et al is the only other approach utilizing BlazePose for classifying physiotherapy exercises [31]. However, there was no emphasis on evaluating exercise performance, and the ML models were not trained or tested on actual patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study [19]suggested a technique for identifying human activity that combined Dynamic time warping and Laban movement analysis (LMA). In this paper [20], the authors have used Convolutional Neural Networks (CNN) alongside Support Vector Machine (SVM) on the time series data for exercise performance evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VideoPose [ 12 ]/PoseLifter [ 18 ]) exists but is generally not directly suitable for rehabilitation/sporting applications. Very recently, BlazePose [ 11 ] was applied in physiotherapy exercise classification [ 19 ], but the predictive capacity for individual joint angles was not clear. Further a new two-camera approach combining 2D keypoint estimation from OpenPose to lift to 3D yielded good accuracy in assessing mean absolute error in joint angles in a variety of activities, including walking and squatting and jumping [ 20 ], although the accuracy of individual metrics of interest to physiotherapists was not presented, and a calibration step is needed to combine the output from the two cameras.…”
Section: Introductionmentioning
confidence: 99%